Forty years on the fenceline: community, memory, and chronic contamination. Issue 2 (3rd April 2018) - Adams, Alison E.; Shriver, Thomas E.; Saville, Anne; Webb, Gary
ABSTRACT: Residents living next to polluting industries are particularly vulnerable to toxic exposures and environmental illness. Cases of industrial contamination are shrouded in ambiguity and etiological uncertainty, making it difficult to delineate how residents understand their exposure and illness experiences. We analyze the case of Ponca City, Oklahoma to examine how residents' collective memories and shared narratives inform their interpretations of long-term petrochemical exposure over a period of 40 years. The data for this project include: oral histories with residents; local media coverage regarding the contamination; and archival documents and artifacts that spanned this time frame. Our historical analysis of the case provides insights into how residents relied on lay ways of knowing to make sense of their exposure and illness experiences over time. We conclude by discussing the utility of examining collective memory in communities facing longstanding contamination and illness.